Evidence for a fading affect bias in subjectively assessed affect changes in autobiographical memory - Hoehne, Sophie; Zimprich, Daniel (Frontiers in Psychology, 2025)
IntroductionOver time, autobiographical memories (AMs) can decrease in affect intensity (fading affect), increase in affect intensity (flourishing affect), remain the same (fixed affect), or change valence (flexible affect). In this regard, the fading affect bias (FAB) names the phenomenon that, on average, negative AMs’ affect intensity fades more strongly and more rapidly over time than positive AMs’ affect intensity, which sometimes even increases on average. The FAB has most often been investigated using difference scores between retrospective ratings of AMs’ initial affect intensity and their affect intensity from a current perspective (calculated change). The goal of the present study was to complement this previous research by additionally investigating the FAB in subjective change, that is, the directly assessed, subjectively perceived direction of affect change in an AM over time.MethodMixed-effects multinominal models were used to predict the probabilities of the different types of subjective change, which were then compared with their likelihood in calculated change. Moreover, the influence of initial intensity, neuroticism, and life satisfaction was compared between subjective change and calculated change. Analyses were based on 12,314 AMs reported by 2,163 adults aged 18–98 years.ResultsA clear FAB was found for both subjective and calculated change. Neuroticism and life satisfaction showed comparable effects on subjective and calculated change, but the effects of initial intensity differed. Specifically, the effects of initial intensity on the probability of flourishing and flexible affect in subjective change were in the same direction as for calculated change, albeit with substantially weaker effect sizes. Moreover, only for subjective change did initial intensity have an effect on the likelihood of fading affect (negative effect).DiscussionThe present findings extend previous knowledge of the FAB and its predictors, particularly with regard to initial intensity. Moreover, the present study supports the idea of an emotion-regulating, self-serving functionality of autobiographical memory, also within subjective emotional changes, and sheds an optimistic light on the appropriateness of retrospective designs in FAB studies.